Study on shear characteristics of calcareous sand with different particle size distribution - Zhang, Yongtao; Zhang, Ruiyuan; Yu, Chengcheng; Luo, Huiwu; Deng, Zhiqiang (Frontiers in Earth Science, 2023)
For the island and reef project formed by filling calcareous sand, the problems of wide particle size distribution (PSD) and complex mechanical properties have to be faced. Therefore, in order to provide basic mechanical parameters for the construction of the island and reef project, triaxial shear tests were carried out on calcareous sands with five different typical PSDs. The results showed that as particle gradation became narrower, the axial strain corresponding to the strain-softening point all showed a decreasing trend and their differences gradually decreased; the confining pressure has a significant impact on the volumetric deformation modulus of calcareous sand with a wide PSD. The cohesion of calcareous sand showed a positive correlation with non-uniformity and curvature coefficients, while the variation of an internal friction angle showed a parabolic law; the internal friction angle also changes in the parabola with the change of fine particle contents. Furthermore, by establishing the PFC3D discrete element model, it was found that the numerical simulation results were in good agreement with the test results, which verifies the feasibility of the numerical simulation and the rationality of the mesoscopic parameter calibration. It was discovered that the wider the particle gradation range, the greater the axial strain corresponding to the critical coordination number; the sample with a narrow gradation interval was more likely to present a rotating displacement field to form a penetrating shear band. This study can provide design parameters for stability analysis of high and steep slopes in calcareous sand sites.